Social networks and sexual behaviour: towards a relational approach to sexuality, risk-taking behaviour and prevention practices - Aboim, Sofia (Saúde e Sociedade, 2011)
Based on a representative survey of the Portuguese population aged between 18 and 65, carried out in 2007, this study investigates the impact of social networks on the sexual behaviour of individuals. Through the normative perceptions respondents have of the sexual morals of their family members and friends, as well as through a number of indicators related to the characterization of the network of sexual confidants, such as number, identity, gender, age and confidants' behaviour in terms of sexuality and risk-taking practices, we were able to draw a multidimensional portrait of the individuals' social networks. By carrying out several linear and logistic regression analyses, we were also able to evaluate the predictive power of network variables and their effect on the number of sexual partners, occasional sex and condom use. Data show that network factors are important to explain individuals' sexual behaviour. Confidence networks constituted by friends and orientated towards a more liberal sexual moral tend to allow for a greater sexual experimentalism, particularly in the case of women. On the other hand, the homology between confidants' and respondents' sexual behaviour seems relevant to explain condom use in occasional sex, especially in the case of men. Either by taking on a relational perspective or an epidemiological approach, the analysis of individuals' social networks constitutes a major feature for understanding and explaining the variety of sexual experiences and the infection risks that can be associated with sexual behaviour.